Data Plaza: An interoperable platform for combining, analyzing, and visualizing research open data - Quirós, Carlos F.; Arnaud, Elizabeth; Laporte, Marie-Angélique; Sousa, Kauê de; Etten, Jacob van (2023)
The Data Plaza is a new interoperable community platform for merging, analyzing, and visualizing research open data. The first Data Plaza prototype was developed for the Digital Innovation initiative and currently stores very simple metadata with interoperable connection to the data source. The objective is for this platform to become a one CGIAR data analytics platform and support making data ready fo artificial intelligence.